Cardiac biomarkers in coronary slow flow: Endocan and omentin-1 - Kaan Okyay (KARE Publishing, 2019)
In the current issue of Archives of Turkish Society of Cardiology Journal, Sigirci et al., have evaluated serum endocan and omentin-1 levels in patients diagnosed with stable angina pectoris who had coronary slow flow phenomenon on angiography. In this editorial comment, the comments on the article are provided.